THU0216 Nsaids self-prescription as a cause of upper gastrointestinal hemorraghe. (1st June 2001) - Rosas, J; Server, E; Ena, J; Romero, A; Valverde, J; García, A; Quílez, C; Vázquez, J; Torres, MT; Simons, B
Abstract : Background: Non-steroidal anti-inflammatory drugs (NSAIDs) are compounds easily to acquire over the counter that are extensively used for symptomatic relieve of pain of any origin and for platelet antiaggregation purposes. Objectives: To describe the epidemiology of NSAIDs usage and its association with upper gastrointestinal hemorraghe in a community hospital from Spain. Methods: We prospectively studied the clinical usage, indication, duration, dose, type of NSAID therapy, presence of NSAIDs self prescription and use of concomitant drugs in all patients admitted to the hospital with upper gastrointestinal haemorrhage from October-1999 to November-2000. All patient underwent endoscopy to assess the type of gastroscopic lesion and the presence of Helicobacter pylori. Requirements of blood transfusion and surgery were also noted. Results: A total 63 (29%) out of 216 patients admitted with upper gastrointestinal haemorrhage were using NSAIDs (60% aspirin, 16% piroxicam, 13% diclofenac, 6% combined and 5% other) during a median of 7.5 days (range 1- >100 days). Median patients´ age was 65 years (range 18–90). NSAIDs were prescribed for pain relieve (75%), platelet anti-aggregation (19%) or both (6%). Indication for prescription was done by rheumathology consultants (0%), general practitioners (25%), other consultants (33%) and self-prescribed (41%). Location of lesions at endoscopy were: esophageal (5%), gastric (35%), duodenal (43%) and, multiple lesions (17%). Helicobacter pylori was present in 28 (70%) out of 40 samples. A total of 44 (70%) patients had at least one risk factor for NSAIDs gastropathy of whom only 2 (4%) were receiving prophylaxis with protein pump inhibitors and 1 (2%) with H2-blockers. NSAIDs gastrointestional haemorrhage accounted for a total of 346 admission days, 40 (63%) patients needed blood transfusion and one (1%) suffered surgery. Conclusion: Self-prescription is a common cause of NSAIDs gastrointestinal haemorrhage. Only a minor proportion of patients with risk factors for NSAIDs gastropathy receive appropriate prophylaxis with protein pump inhibitors.